Numerical Investigation of the Effect of Discrete Ribs on Flow Field and Heat Transfer in a Rectangular Channel - Mohaddes Deylami, Hamed; Hassanzadeh-Aghdam, Mohammad Kazem (Mechanical Technology and Engineering Insights, 2025)
Enhancement of convective heat transfer in internal cooling channels is of great importance in the design of compact heat exchangers, turbine blade cooling passages, and electronic thermal management systems. In the present study, a comprehensive numerical investigation is conducted to analyze the effects of discrete ribs on the flow field and heat transfer characteristics in a two-dimensional rectangular channel. Three different rib geometries, namely triangular, rectangular, and circular ribs, are examined under turbulent forced convection conditions using air as the working fluid. The Reynolds-averaged Navier–Stokes equations coupled with the energy equation are solved using the finite element method implemented in COMSOL Multiphysics. Turbulence effects are modeled using the k–ω SST model to accurately capture flow separation, recirculation zones, and near-wall behavior induced by the ribs. A constant heat flux is applied to the ribbed wall, while the remaining walls are assumed adiabatic. A detailed grid independence study and validation against classical Nusselt number correlations are performed to ensure numerical accuracy. The effects of rib number, rib height, base length, and rib shape on velocity distribution, pressure loss, and Nusselt number are systematically investigated. The results demonstrate that discrete ribs significantly disturb the boundary layer, generate strong vortical structures, and enhance convective heat transfer compared to smooth channels. Increasing the number of ribs intensifies turbulence and heat transfer but also increases pressure losses. Rib geometry is shown to play a critical role: rectangular ribs provide the highest Nusselt number enhancement due to stronger, more persistent vortices. In contrast, shorter ribs reduce pressure penalties with moderate heat transfer improvement. The findings provide valuable insights into the optimal geometric design of ribbed channels for high-performance thermal systems.